Social network analysis and mining: challenges and applications - Fonseca, Bruna P.; Albuquerque, Priscila C.; Zicker, Fabio; Morel, Carlos M. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM); 2021: Anais do X Brazilian Workshop on Social Network Analysis and Mining, 2021)
Social network analysis and mining (SNAM) is a powerful tool to dis- close relevant information hidden in large volumes of raw data. Its application to several research fields, powered by automation and advanced computing infrastructure, expanded its use and brought along new challenges. In this paper, we provide a critical perspective on SNAM’s major challenges, by discussing a few examples. We also address some promising applications that can potentially translate SNAM results into practical knowledge.